2018
DOI: 10.1063/1.5043570
|View full text |Cite
|
Sign up to set email alerts
|

Steep switching in trimmed-gate tunnel FET

Abstract: We propose a tunnel field-effect transistor (TFET) having a trimmed gate (TG) structure, which considerably improves the subthreshold swing (SS). The TG structure truncates the needless long band-to-band tunneling (BTBT) paths to a “channel”, which normally appear in a conventional TFET, and realize a sudden switching to the on-state arising from a short BTBT path. Our simulations demonstrate that the TG-TFET can achieve an extremely steep SS, less than 10 mV/decade, in the double-gated Si-channel configuratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Thus, an abrupt switch from gate-parallel tunneling to gatenormal tunneling while minimizing gate-diagonal tunneling is necessary to improve the SS of gate-normal TFETs. To achieve this, some pioneering research results have been reported [19]- [21]. However, there remains room for the further suppression of gate-diagonal tunneling and its underlying physics have not been discussed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, an abrupt switch from gate-parallel tunneling to gatenormal tunneling while minimizing gate-diagonal tunneling is necessary to improve the SS of gate-normal TFETs. To achieve this, some pioneering research results have been reported [19]- [21]. However, there remains room for the further suppression of gate-diagonal tunneling and its underlying physics have not been discussed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…15) Note that the large SS values exhibited because we employed simple TFET devices in this work, focusing on the impact of IET technology. The SS can be improved by enhancing the gate electrostatic control 36) or employing an advanced device structure, 37) for example.…”
Section: Resultsmentioning
confidence: 99%
“…35) This non-local BTBT model has successfully reproduced the experimental device characteristics of Sichannel TFETs. 12,22,31)…”
Section: Model and Methodsmentioning
confidence: 99%
“…Recently, we have proposed a trimmed-gate (TG) structure which notably improves the average SS by reducing the off leak component of the BTBT current. 22) In previous work, we focused on a double-gated TFET and numerically demonstrated that the TG structure realizes extreme steep switching. Moreover, since the mechanism of steeper switching by the TG structure does not depend on any specific material or process technology, in principle, the TG structure is expected to be applicable to any type of TFET.…”
Section: Introductionmentioning
confidence: 99%